Peran Lembaga Pemasyarakatan Dalam Upaya Rehabilitasi Narapidana Untuk Mengurangi Tingkat Residivis - Mufti, Erlangga Alif; Riyanto, Ontran Sumantri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Correctional Institutions (Lapas) have a role not only as places of sanctions implementation, but also as spaces for transformation aimed at reducing the potential for recurring criminal activities, commonly known as recidivism. The research methodology employed is a juridical-sociological approach, which combines legal analysis and social aspects to elucidate the role of Lapas in the reformation of prisoners. This research delves into the legal foundation governing the responsibilities of Lapas and also analyzes regulations related to prisoner rehabilitation. The findings of the research indicate that Correctional Institutions (Lapas) play a central role in the rehabilitation process of prisoners, including the formulation of rehabilitation programs, education, skills training, and psychosocial approaches. The rehabilitation efforts undertaken by Lapas aid prisoners in skill development, behavioral transformation, and preparation for successful social reintegration. Despite encountering obstacles, Lapas has legal foundations and social practices that support the objectives of implementing prisoner rehabilitation. The challenges confronted by Lapas in conducting rehabilitation, such as limited facilities and social challenges, underscore the importance of synergy between legal and social aspects in comprehending the role of Lapas in addressing the recurring challenges of crime rates through prisoner rehabilitation efforts.